Exploring Alignment: Accounting Undergraduate Students' Self-Perception of Fit within Gojek's Corporate Culture - Wahyudi, Wahyudi (FKIP Universitas Lampung, 2025)
Exploring Alignment: Accounting Undergraduate Students' Self-Perception of Fit within Gojek's Corporate Culture. Objective: This study investigates the fitness of accounting undergraduate students toward Gojek corporate culture, focusing on work flexibility, essential soft skills, perceived fit, and barriers to integration into Gojek corporate culture. Method: Data were collected from 23 students in their final year at Pontianak State Polytechnic. The data is collected using semi-structured interviews to identify the factors influencing their perceived alignment with Gojek's corporate culture. The study applied qualitative research. Findings: The study reveals that Gojek's work flexibility as the key attraction to the students. The students perceive that they have communication and problem-solving skills as essential competencies, yet there is a divide between those who are confident and doubtful of their fitness. The study also reveals that language and cultural understanding as barriers to their fit into Gojek's corporate culture. Conclusion: The findings underscore the importance of work flexibility, communication skills, and problem-solving abilities in shaping students' perceptions of fit. However, barriers such as job demands, language proficiency and cultural competencies indicate areas where further development is needed. Therefore, an integrated curriculum and targeted training are needed to increase students' language skills, especially English, and cultural competency to prepare them for a multinational company culture like Gojek. Keywords: accounting students, corporate culture, gojek, po fit, generation z, soft skills.